Everyone's public relations work - Communication Briefing (Blackwood, N.J. : Communication Briefing, 1991)
This video defines role of every person in a organization and shows employees how they can contribute to the organization's public relations effort.
Presenter: Ann H. Berkelew
Keywords: Public relations -- Management; Communication in organization